2010
DOI: 10.1111/j.1749-8198.2010.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Challenges of Climate Science Literacy: Lessons from Students, Teachers and Lifelong Learners

Abstract: Today more than ever, being climate literate is a critical skill and knowledge area that influences our interaction with the environment around us, our understanding of scientific news and the daily decisions that we make. Yet, the term climate literacy can be misunderstood, as are the terms weather, climate and climate variability. This article surveys the existing literature and highlights six challenges to achieving a climate literate citizenry in both formal and informal or lifelong learning. The lessons l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 16 publications
0
23
0
2
Order By: Relevance
“…As part of this pedagogical process, it is important to bear in mind that climate change is a complexly anthropogenic problem- Harlan et al, 2015;Lotz-Sisitka, 2010;Schlosberg & Collins, 2014;Shue, 2014;Zeidler & Newton, 2017). One direct way for courses to draw in and draw on some of these themes is to discuss (and develop activities around) how demographic groups and geographic regions are asymmetrically implicated in and impacted by climate change, helping students to understand that "those countries"-and populations-"most at risk from the consequences of climate change are ironically and paradoxically also the ones that have contributed least to climate change" (Lotz-Sisitka, 2010, p. 72; see also Cuomo, 2011;Whyte, 2014). In this vein, increased classroom attention to climate justice promises not only to foreground the ethical stakes and implications of climate change, but also to shift the curricular focus of introductory courses toward a more writerly climate literacy, attentive to the need and potential for intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of this pedagogical process, it is important to bear in mind that climate change is a complexly anthropogenic problem- Harlan et al, 2015;Lotz-Sisitka, 2010;Schlosberg & Collins, 2014;Shue, 2014;Zeidler & Newton, 2017). One direct way for courses to draw in and draw on some of these themes is to discuss (and develop activities around) how demographic groups and geographic regions are asymmetrically implicated in and impacted by climate change, helping students to understand that "those countries"-and populations-"most at risk from the consequences of climate change are ironically and paradoxically also the ones that have contributed least to climate change" (Lotz-Sisitka, 2010, p. 72; see also Cuomo, 2011;Whyte, 2014). In this vein, increased classroom attention to climate justice promises not only to foreground the ethical stakes and implications of climate change, but also to shift the curricular focus of introductory courses toward a more writerly climate literacy, attentive to the need and potential for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, students arrive in courses with prior knowledges, beliefs, conceptual frameworks, and misconceptions that influence their engagements with course materials, and affect whether and how they learn course content (see, e.g., Aksit, McNeal, Gold, Libarkin, & Harris, ; Chi, ; Gilbert & Watts, ; Rissler, Duncan, & Caruso, ). Students' classroom engagements with climate change are no exception to this rule (Dupigny‐Giroux, ; Lombardi & Sinatra, ). Previous research on college students has found that students generally agree that climate change is happening, but that they also harbor misconceptions regarding climate change (see, e.g., Pfautsch & Gray, ; Wachholz, Artz, & Chene, ).…”
Section: Introductionmentioning
confidence: 99%
“…With a topic that is inherently complex and nonintuitive (McCaffrey & Buhr, 2008) the challenge in teaching climate change lies in on how to integrate misconceptions in mainstream pedagogical practices. Indeed, it had been reiterated that misconceptions bar efforts at improved climate literacy (Harrington, 2008;Dupigny-Giroux, 2010).…”
Section: Misconceptions and Climate Changementioning
confidence: 97%
“…Furthermore, previous research using phenology as a teaching aid has been limited in the extent to which it has highlighted its possible application in this context [16][17][18]. In the present study, we focused on school-based education, which is an important source of information for children on climate change [19]. We postulated that creating an environment where time-lapse images can be used to observe plant phenology in the classroom would allow more children to enhance the readiness of behavior toward resolution of climate change issues.…”
Section: Time-lapse Images and Release On The Internetmentioning
confidence: 99%